PENGARUH KELOMPOK WANITA TANI TERHADAP PENDAPATAN KELUARGA TANI DI DUSUN PANDEREJO DESA SIMOREJO-WIDANG-TUBAN - Bela Mufaridiyah Ma’rufah,; Astuty, Henny Sri (Istiqra: jurnal hasil penelitian, 2023)
This research aims to determine the influence of women farming groups on increasing the income of farming families in Panderejo Hamlet, Simorejo Widang Village, Tuban. This research is quantitative. The population in the study were all members of the women's farmer group in Panderejo Hamlet, Simorejo Widang Tuban Village, totaling 44 people. Data collection techniques use questionnaires. The sample was determined using a saturated sampling technique or census method. Data analysis techniques use the Validity Test, Reliability Test, Normality Test, Simple Linear Regression, T-test, and Coefficient of Determination. Based on the normality test results, it shows that the correlation value is 0.634. Meanwhile, the results of simple linear regression analysis show that the influence of women farming groups on increasing farming family income is 40.2%, while the remaining is 59.8%. Meanwhile, the participation of women farmer groups was 5,313, where the value was above T -table 2.018 and the T -calculated probability value was 0.000, which was below 0.05. From the results of the statistical analysis above, it can be concluded that the group of women farmers has a significant partial influence on the income of farming families in Panderejo Hamlet, Simorejo Village, Widang Tuba.